2005
DOI: 10.1111/j.1610-0387.2005.05725.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinico‐pathological approach to the classification of human demodicosis

Abstract: We suggest that demodicosis be divided into both primary and secondary types. The usual etiological agent of primary demodicosis is D. folliculorum, which causes an erythemato-squamous eruption in the facial T-zone. The rash starts on unaltered skin and covers 8 - 15 % of the face. Pruritus accompanies the onset of the rash, while erythema is first apparent after papulo-pustules are seen and disappears after treatment. Half the patients show seasonal exacerbations. Secondary demodicosis is usually caused by D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…They also found higher prevalences of D. folliculorum infestation in the forehead and nose region than on the cheeks and chin region. This finding concurs with those of Akilov et al24, who concluded D. folliculorum is more likely to cause demodicosis in the facial T-zone. These results indicated that the development of sebum secretion and the dilation of follicle in the T-zone are attributable to the proliferation of D. folliculorum , and that this increases the detection rate of SSSB.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They also found higher prevalences of D. folliculorum infestation in the forehead and nose region than on the cheeks and chin region. This finding concurs with those of Akilov et al24, who concluded D. folliculorum is more likely to cause demodicosis in the facial T-zone. These results indicated that the development of sebum secretion and the dilation of follicle in the T-zone are attributable to the proliferation of D. folliculorum , and that this increases the detection rate of SSSB.…”
Section: Discussionsupporting
confidence: 93%
“…The first is that pityriasis folliculorum is usually caused by the more superficially living D. folliculorum , whereas rosacea type is commonly associated with the deep living D. brevis 24. The second is that measurements are usually performed using severe lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeper and larger [102,105,113] Pruritus Usually considered more frequent in demodicosis [70,72,74,79,241,242,99] Evolution over time The 2 forms may occur successively in the same patient [10] Often after pityriasis folliculorum More often after ETR than the reverse [8,57,136] Treatment Acaricide Anti-inflammatory, acaricide of benzyl benzoate (with crotamiton) on Demodex density and on clinical symptoms in a real-life study [159,160]. In our practice, we successfully used benzyl benzoate (with crotamiton) cream for more than 20 years; however, the development of ivermectin has provided an effective alternative [172,223,224] with better tolerance and this is now our treatment of choice.…”
Section: More Superficial and Smallermentioning
confidence: 99%
“…Signs and symptoms of the disease are present (erythema, pruritus, etc. ), this clinic course is thought to be induced by D. brevis [19].…”
mentioning
confidence: 99%